Structure and modes of dc glow discharge in nitrogen with hollow cathode or anode - Lisovskiy, V.A.; Osmayev, R.O.; Khilko, D.I.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2018)
This paper studies the modes of burning and structure of the glow discharge with "hollow cathode and flat anode" and "hollow anode and flat cathode" in nitrogen. We have demonstrated that a higher discharge current is observed with a hollow cathode because its area exceeds 3 times that of a flat one. The discharge with a hollow cathode may burn in hollow or glow modes (with the cathode cavity filled with negative glow or not). We have measured the axial profiles of the emission line intensities for nitrogen molecules, atoms and ions with different gas pressure, discharge current values and electrode designs. We have observed the high intensity of the emission lines of the atomic nitrogen in the cathode sheath near the surface of the flat cathode indicating a remarkable dissociation degree of nitrogen molecules in this region of the discharge.